PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH DAN AKTIVITAS BELAJAR MATEMATIKA KELAS VIII MELALUI PENERAPAN MODEL PEMBELAJARAN TSOI - Ni Nengah Mardiani .; Prof. Dr.I Gusti Putu Suharta,M.Si .; Drs.Djoko Waluyo,M.Sc . (Jurnal Pendidikan Matematika Undiksha, 2015)
Penelitian ini bertujuan untuk mengetahui peningkatan kemampuan pemecahan masalah matematika, serta mengetahui peningkatan aktivitas belajar matematika siswa melalui penerapan model pembelajaran TSOI. Penelitian ini adalah Penelitian Tindakan Kelas yang melibatkan subjek sebanyak 38 orang siswa Kelas VIII 14 SMP Negeri 2 Singaraja pada semester genap Tahun Pelajaran 2014/2015. Penelitian ini dilakukan dalam tiga siklus yang masing-masing terdiri atas tahap perencanaan, pelaksanaan tindakan, observasi/evaluasi serta refleksi. Pengumpulan data menggunakan metode wawancara, observasi dan tes. Keseluruhan data ini selanjutnya dianalisis secara deskriptif. Hasil penelitian menunjukan kemampuan pemecahan masalah matematika siswa dan aktivitas belajar matematika siswa meningkat. Rata-rata skor kemampuan pemecahan masalah matematika siswa pada refleksi awal yaitu 38,33 pada siklus I rata-rata nilai kemampuan pemecahan masalah matematika meningkat menjadi 48,65 meningkat lagi menjadi 65,2 pada siklus II dan meningkat menjadi 78,2 pada siklus III. Rata-rata skor 41,73 meningkat lagi menjadi 49,43 pada siklus II dan meningkat menjadi 64,46 pada siklus III. Peningkatan tercapai setelah siswa melalui tahapan-tahapan pembelajaran dari penerapan model pembelajaran TSOI dengan beberapa penyemprunaan pada tindakan pembelajaran.Kata Kunci : model pembelajaran TSOI, kemampuan pemecahan masalah, aktivitas belajar matematika This study aimed at knowing students’ achievement of mathematics solving problem skill and learning activity through the implementation of TSOI learning model. This study is classroom action research which involving 38 students of class VIII 14 SMP Negeri 2 Singaraja in even semester in the academic year 2014/2015 as subject. This study was done in three cycles, in which each cycle consisted of planning, acting, observing, and reflecting. The data were collected by using interview, observation and test. Then, the data were analyzed descriptively. The results of the study show that the students’ achievement of mathematics solving problem skill and learning activity increase. The average of students’ mathematics solving problem score in the beginning reflection was 38,33. In the first cycle, the average of students’ mathematics solving problem score increased to 48,65. Then, in the second cycle, the average of students’ mathematics solving problem score increased to 65,2. Finally in the third cycle, the average of students’ mathematics solving problem score increased to 78,2. However, the average of students’ mathematics learning activity score in the beginning reflection was 28,81. In the first cycle, the average of students’ mathematics learning activity score increased to 41,73. Then, in the second cycle, the average of students’ mathematics learning activity score increased to 49,43. Finally in the third cycle, the average of students’ mathematics learning activity score increased to 64,46. The improvement achieved after the students passed the learning steps of TSOI with some perfections in the action learning. keyword : TSOI Learning Model, Solving Problem Skill, Mathematics learning Activity